- #1
jasonjinct
- 7
- 0
Please help me explain how to solve this to find the unilateral laplace transform
x(t)=tu(t) - (t-1)u(t-1) - (t-2)u(t-2) + (t-3)u(t-3)
I know the part tu(t)
as a(t) = u(t) --> 1/s
then b(t) = tu(t) ---> - d/dx a(t) = 1/s^2
But for those (t-1), (t-2) in front u(t), how to solve these?
Please help me, thank you very very much
x(t)=tu(t) - (t-1)u(t-1) - (t-2)u(t-2) + (t-3)u(t-3)
I know the part tu(t)
as a(t) = u(t) --> 1/s
then b(t) = tu(t) ---> - d/dx a(t) = 1/s^2
But for those (t-1), (t-2) in front u(t), how to solve these?
Please help me, thank you very very much